Aplicações da teoria de Piaget ao ensino da matemática elementar - Melo, Magda Ivonete Montagnini (1980)
The aim of this study is the application of Jean Piaget's experimental and theoritical principles to the teaching of mathematics. Having in view the educational implications of the theory, we presented a proposal to systematize a teaching technique which aims at activating the mental structures through teaching mathematics. In summary, this work constitutes a synthesis of Piaget's theory of cognition development, and the cription of an experimental research which has the objective of evaluating the results of this methodology in activating the mental structures of the child. With this aim in view, two working groups formed (the experimental and the contron groups), were both with 21 students from medium superior and medi um inferior social classes, who were students of the second grade of private elementary schools in the city of Goiania (GO). To both groups an initial test was applied. During a teaching semester, the Piagetian methodology was applied in the teaching of mathematics of the experimental group, and, to the control group, a tradition methodology was utilized. After this work was done, a post-test was applied to both groups. A comparative study of the resulta obtained led us to verify the efficiency of the proposed methody and the fecundity of the teaching of mathematics under a Piagetian perspective.